Educating Teachers for Diversity: Meeting the Challenge (OECD Publishing, 2010)
This publication summarises key research findings which can be used to redesign initial and continuing teacher education to help practitioners effectively teach diverse students. It looks at challenges teachers face in OECD countries and presents a range of policies and practices used in various contexts, from countries with long histories of diversity to those with more recent experiences. The key role of evaluation – of teachers, schools and systems – is emphasised. Educating Teachers for Diversity: Meeting the Challenge asks how these insights can inspire continuing educational reform for our changing classrooms, with a special focus on key questions for research, policy and practice.
Keywords: Interkulturelle Erziehung; Interkulturelles Lernen; Lehrerfortbildung